Pemanfaatan Kembali Botol Plastik Sebagai Komponen Paving Block - Jojo Sumarjo; Siswadi Siswadi (Fakultas Teknik, Universitas Singaperbangsa Karawang, 2025)
The village of Kiara, located at the eastern end of Karawang, has been facing a significant issue with waste production, particularly from food scraps and disposable plastics. In response, a project was launched to create paving blocks using plastic waste, providing an economic value to the community. The first step in this initiative involves educating the public about the characteristics of plastic waste and its harmful effects on health and the environment. Following this socialization, a team will assist in setting up four designated waste collection sites. The aim is for residents to sort their waste at the household level, separating organic from non-organic waste for further processing. The second phase of the solution focuses on training the community to convert plastic waste into paving blocks. Educating the public on proper plastic waste management is key to this process. However, challenges persist, particularly with the tools needed to expedite the production of paving blocks, such as waste disposal equipment and block-pressing machines. The village hopes to acquire these tools in the future to improve the efficiency of the production process, saving both energy and time. Despite these challenges, the program has successfully raised awareness, and the community now has a better understanding of how paving blocks are made from plastic waste.